The vicus of Bedriacum: notes on landscape archaeology (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2022)
Bedriacum was settled at the intersection of waterways and land routes, on a hill for a safe ford on the river Ollius. During the archaeological investigations carried out in the last century, non-invasive analyses of the area were also conducted. They led to a geological definition of detail and allowed an overview with aerial photographs; with subsoil analysis carried out through geophysical prospecting, and an overview given by constant comparison with historiographic sources. In view of the new investigation season that is looming for the vicus, here is a quick review of the publication and archival data of the non-invasive investigations conducted on several occasions, for a first reading of the archaeological landscape of Calvatone-Bedriacum.
Keywords: Bedriacum; vicus; geophysical analysis; aerial photos; geomorphological analysis; survey